2005
DOI: 10.4028/www.scientific.net/kem.291-292.177
|View full text |Cite
|
Sign up to set email alerts
|

Energy-Mode Adjustment in Laser Processing a Small Vitrified CBN Grinding Wheel

Abstract: A study of the energy-mode adjustment and application was presented to investigate the effects of adjustable methods on energy mode. Three methods of energy-mode adjustment were used: by circular profile itself, by an optical scanning expander and deformable mirror. The circular profile naturally modifies energy density with the changes of incident angle. The optical scanning expander was used to turn a Gaussian beam into a uniform beam. Also a novel technique of deformable mirror was designed to obtain a more… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
3
1
1

Relationship

2
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…Energy absorption and conduction models were developed by Wang et al (2005a), Wang et al (2005b), Wang et al (2005c) and Wang and Wang (2003), which take into account the laser energy absorbed by the surface of the wafer. It is assumed that the laser energy is absorbed by the entire material in the element in accordance with the energy balance equation.…”
Section: Finer Finite Element Methodsmentioning
confidence: 99%
“…Energy absorption and conduction models were developed by Wang et al (2005a), Wang et al (2005b), Wang et al (2005c) and Wang and Wang (2003), which take into account the laser energy absorbed by the surface of the wafer. It is assumed that the laser energy is absorbed by the entire material in the element in accordance with the energy balance equation.…”
Section: Finer Finite Element Methodsmentioning
confidence: 99%
“…For laser conditioning of wheels, the tangential irradiation and the radial irradiation are two typical configurations. Research from Wang et al [19,26] showed that the absorbed energy of grinding wheels changed significantly at different radial positions and incident angles, because the space distribution of absorbed and scattered energy was far more different during laser irradiation. Therefore, the laser head should move along with the grinding wheel axis in order to keep the focus offset constant.…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the tangential irradiation aims to prepare the grinding wheel with more accurate profile. Research from Wang et al [23,30] showed that the absorbed energy for grinding wheels changed significantly at different radial position and incident angle because the space distribution of absorbed and scattered energy was far more different during laser irradiation. Therefore, the laser head should move along with the grinding wheel axis in order to keep the focus offset constant.…”
Section: Introductionmentioning
confidence: 99%